KARAKTERISASI PELIKEL YANG TERADSORPSI PADA PERMUKAAN RESIN AKRILIK - Siti Sunarintyas; Dyah Irnawati (Journal of Dentistry Indonesia, 2015)
This research was aimed to determine the composiiton of adsorbed pellicle on acrylic resin surface. Fifteen plates of 10x10x2 mm were made from chemical, heat, and microwave activated acrylic resin. The plates were incubated in saliva for 1,2,3,4, and 5 hours. Pellicle characterization was done every hour by SDS PAGE electrophoresis. The result showed that: 1. chemical, heat, and microwave activated acrylic resin adsorbed salivary pellicle by molecular weight of 50-61 kDa (amylase band); 2. incubation of 1,2,3,4, and 5 hours in saliva resulted in similar pellicle composition. In conclusion, adsorbed salivary pellicle on acrylic resin surface during 5 hours showed similar characteristic in every hour, with the major protein adsorbed: amylase.